Performance enhancement of gel polymer electrolytes using sulfonated poly(ether ether ketone) for supercapacitors. Issue 8 (3rd February 2021) - Li, Guoqiang; Yang, He; Zuo, Danying; Zhang, Hongwei
Abstract: Gel polymer electrolytes (GPEs) with reasonable mechanical properties are highly favorable for flexible/stretchable solid‐state supercapacitors. However, the widely explored poly(acrylic acid) (PAA)‐based GPEs provide unsatisfactory mechanical performance. Herein, a useful strategy is adopted to improve the performance of PAA‐based GPEs by incorporating sulfonated poly(ether ether ketone) (SPEEK) chains. The optimum SPEEK‐enhanced PAA GPE shows an ionic conductivity of 100 ± 1.57 mS cm −1, ultimate tensile strength of 4.2 ± 0.24 kPa and elongation at break of 858%, which are larger than those of the plain PAA GPE. A supercapacitor developed using such a SPEEK‐enhanced GPE also delivers higher specific capacitance, larger energy density and comparable cycling stability compared to a supercapacitor using a PAA GPE. This work suggests that rigid ionic polymers are suitable for improving the performance of GPEs with inferior mechanical properties. © 2021 Society of Chemical Industry Abstract : A SPEEK‐enhanced PAA‐based gel polymer electrolyte with improved mechanical properties is studied for use in an electric double‐layer capacitor.